Pengaruh Media Belajar Smartphone Terhadap Belajar Siswa Di Era Pandemi Covid-19: (The Influence of Smartphone Learning Media on Student Learning in The Era Pandemi Covid-19) - Sulaiman, Jauharil Maknuni (Indonesian Educational Administration and Leadership Journal (IDEAL), 2020)
The era of the Covid 19 pandemic has changed the teaching and learning process from the face-to-face stage at school to distance learning at home. This effort is to break the spread of covid 19. Of course a means is needed to support an effective teaching and learning process, this study aims to see the influence of smartphone learning media. on student learning in the Covid 19 pandemic era.The formulation of the problem in this study is to determine the effect of smartphone learning media in the covid-19 pandemic era, the benefits of smartphone learning media in the pandemic era and the obstacles faced by students in the teaching and learning process using smartphones in the current pandemic era . The methodology in this research is descriptive qualitative, with a phenomenological approach. By collecting data using observation, interviews and documentation. From the research results, it was found that smartphone learning media was very influential in the teaching and learning process in the pandemic era, and this is one of the effective media for distance learning as it is today, and the benefits that students get by using smartphones a) as student learning media b). As an information center c). Adding student insight d) and tools to facilitate communication. And the obstacles faced by students a) students have to spend money to buy internet packages when studying b) students who do not have smartphones c) students lack motivation when studying at home. The benefit of this research is to provide information on learning media using smartphones which are very effective in the era of the Covid 19 pandemic. Abstrak. Era pandemin covid 19 telah mengubah proses belajar mengajar dari tahap tatap muka di sekolah hingga belajar jarak jauh dirumah upaya ini untuk memutus ratai penyebaran covid 19. Tentu dibutuhkan sarana untuk menunjang proses belajar mengajar yang efektif, penelitian ini bertujuan untuk melihat pengaruh media belajar smartphone terhadap belajar siswa di era pandemi covid 19. rumusan masalah dalam penelitian ini untuk mengetahui pengaruh media belajar smartphone di era pandemi covid 19, manfaat media belajar smartphone di era pandemi dan kendala yang dihadapi siswa dalam proses belajar mengajar dengan menggunakan smartphone di era pandemi saat ini. Metodelogi dalam penelitian ini adalah kualitatif deskriptif, dengan pendekatan fenomenologi. Dengan pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Dari hasil penelitian ditemukan media belajar smartphone sangat berpengaruh dalam proses belajar mengajar di era pandemi, dan ini salah satu media yang efektif untuk belajar jarak jauh seperti saat ini, dan manfaat yang di dapatkan siswa dengan menggunakan smartphone a) sebagai media belajar siswa b). Sebagai pusat informasi c). Menambah wawasan siswa d) dan alat untuk memudah komunikasi. Dan kendala yang dihadapi siswa a) siswa harus mengeluarakan uang untuk menbeli paket internet pada saat belajar b) siswa yang tidak mempunyai smartphone c) kurang motivasi siswa pada saaat belejar di rumah. Manfaat penelitian ini untuk memberi informasi media belajar menggunakan smartphone sangat efektif di era pandemi covid 19.Â 